The Immobilization of fluorides from spent carbon cathode in a copper smelting slag - Lei Li; Wu, Guodong; Tian, Fengguo (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
The fluorides from spent carbon cathodes could be effectively solidified in a molten copper smelting slag (FeO-Fe3O4-SiO2-CaO-Al2O3) in forms of CaF2 and Ca4Si2F2O7. The results of thermodynamic analysis, chemical analysis, and XRD and EPMA analyses showed that the F solidification efficiency increased with the CaO amount and decreased with the addition of Al2O3 and SiO2. In addition, it was noteworthy that the F solidification efficiency decreased with an excessive CaO amount, which could be ascribed to the consumption of SiO2 through forming CaSiO3 and Ca3Si2O7. It restricted the solidification of the fluoride into Ca4Si2F2O7. Under the conditions of melting temperature of 1300°C, residence time of 60 min, and N2 flow rate of 40 ml/min, the optimum CaO and NaF amounts were found to be 20 wt.% and 6 wt.%, respectively, in which the F solidification efficiency in the copper smelting slag of FeO-Fe3O4-SiO2-CaO-Al2O3 obtained 98.35%.